2020
DOI: 10.2147/jmdh.s283166
|View full text |Cite
|
Sign up to set email alerts
|

<p>Patient Participation in Multidisciplinary Tumor Conferences from the Providers’ Perspective: Is It Feasible in Routine Cancer Care?</p>

Abstract: Objective: Recent studies from Germany show that a small amount of breast and gynecological cancer patients participate in multidisciplinary tumor conferences (MTCs) at some cancer centers. One reason for the variation by center might be the providers' attitudes about and experiences with MTC patient participation (MTCpp), which has not been analyzed before. Therefore, it is the aim of this study to analyze the providers' expected or experienced feasibility concerning MTCpp at breast and gynecological cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 54 publications
(69 reference statements)
0
26
0
1
Order By: Relevance
“…The extended board may also encompass nuclear medicine specialists, nutritionists, palliative and rehabilitation care physicians, patients' advocacy representatives, research nurses, or other specialists, and in academic centers also students and postdoctoral fellows [6]. Very recently, a cross-sectional qualitative interview study on breast and gynecological cancer MTB explored patients' participation in tumor conferences at six cancer centers in Germany with conflicting results [7]. Besides the fact that half of the health providers had no experience in such settings, the study concluded that routine patients' participation in MTD was not feasible due to providers' barriers and negative experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The extended board may also encompass nuclear medicine specialists, nutritionists, palliative and rehabilitation care physicians, patients' advocacy representatives, research nurses, or other specialists, and in academic centers also students and postdoctoral fellows [6]. Very recently, a cross-sectional qualitative interview study on breast and gynecological cancer MTB explored patients' participation in tumor conferences at six cancer centers in Germany with conflicting results [7]. Besides the fact that half of the health providers had no experience in such settings, the study concluded that routine patients' participation in MTD was not feasible due to providers' barriers and negative experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The consideration of including the patient in MDT meetings must take into account various factors. These include the healthcare provider’s view and what they are willing to discuss in front of the patient, 7 as well as how much the patient may contribute or hinder the conversation. A potential benefit to including the patient would be to allow them to ask questions or share their treatment preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Selection of the patients to include in an MDT must be prioritized to those that have a complex history and need for a variety of expertise. 7 It is necessary to bring the relevant information quickly to the clinician to make the best decision for the patient. Virtual MDT meetings have been emerging as essential to deliver optimal healthcare for complex cases in a remote setting, 8 with examples of clinicians stating that virtual MDTs provide the same standard of care as face-to-face MDTs.…”
Section: Introductionmentioning
confidence: 99%
“…Dies kann beispielsweise durch die Einbindung von Pflegepersonal (Knötgen 2020;Rosell et al 2018) oder die Teilnahme von Patientinnen und Patienten an MTK (Diekmann et al 2020;Heuser et al 2019;Bate et al 2019;Hahlweg et al 2015) erreicht werden. Letzteres wird wiederum nur in einzelnen Zentren umgesetzt und von der Ärzteschaft unterschiedlich bewertet (Heuser et al 2020).…”
Section: Ergebnis Und Umsetzung Der Mtk-empfehlungunclassified